1998
DOI: 10.1182/blood.v91.9.3134
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Knocked-In AML1-ETO Leukemia Gene Inhibits the Establishment of Normal Definitive Hematopoiesis and Directly Generates Dysplastic Hematopoietic Progenitors

Abstract: The t(8;21)-encoded AML1-ETO chimeric product is believed to be causally involved in up to 15% of acute myelogenous leukemias through an as yet unknown mechanism. To directly investigate the role of AML1-ETO in leukemogenesis, we used gene targeting to create anAML1-ETO “knock-in” allele that mimics the t(8;21). Unexpectedly, embryos heterozygous for AML1-ETO(AML1-ETO/+) died around E13.5 from a complete absence of normal fetal liver–derived definitive hematopoiesis and lethal hemorrhages. This phenotype was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 279 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…This is in line with previous data from the Danish Cytogenic Register showing that leukemia constituted 97% of malignancies in trisomy 21 in the first 15 years of life [32]. Some of the genes on chromosome 21 have been found to be disrupted in leukemia [37]. This damage might have been boosted by ionizing radiation in our cohort.…”
Section: Discussionsupporting
confidence: 93%
“…This is in line with previous data from the Danish Cytogenic Register showing that leukemia constituted 97% of malignancies in trisomy 21 in the first 15 years of life [32]. Some of the genes on chromosome 21 have been found to be disrupted in leukemia [37]. This damage might have been boosted by ionizing radiation in our cohort.…”
Section: Discussionsupporting
confidence: 93%
“…However, mutations of RUNX1 are detected in hematological malignancies frequently and less frequently in some solid tumors. In clinical studies, ~10% of AML patients were identified to have translocations near the RUNX1 chromosomal region [ 96 , 97 ], ~7% of esophageal cancer patients had RUNX1 deletion mutations [ 98 ], and ~4% of breast cancer patients had RUNX1 inactivating mutations ( Table 2 ) [ 17 ]. In some hematological malignancies, RUNX1 proteins have been found to fuse with other genes, such as RUNX1-ETO fusion in 10–20% of AML patients and TEL-RUNX1 fusion in 20–25% of childhood ALL patients [ 65 , 99 ].…”
Section: The Regulation Of Runx Proteins In Cancermentioning
confidence: 99%
“…Modeling AML driven by CBF rearrangements such as the RUNX1‐RUNX1T1 (initially referred to as AML1‐ETO ) or the CBFbeta‐MYH11 fusion genes turned out to be rather difficult. Conventional knock‐in models were hampered by embryonic lethality due to the dominant‐negative impact of the fusion to wild‐type RUNX1 and CBFbeta, both essential regulators of adult hematopoiesis 48–50 . Conditional knock‐in mice demonstrated that whereas expression of the CBFbeta‐MYH11 fusion resulted in spontaneous AML after long latency, expression of RUNX1‐RUNX1T1 seemed insufficient to induce an AML phenotype 51–53 .…”
Section: Modeling the Cellular Origin Of Non‐mll Fusion Aml In Micementioning
confidence: 99%